Infant pulmonary function testing in chronic pneumonitis of infancy due to surfactant protein C mutation. Issue 6 (9th March 2015) - Hevroni, Avigdor; Goldman, Aliza; Springer, Chaim
Summary Pulmonary function testing is a vital tool in evaluation and management of adult ILD patients and is rarely overlooked during workup. However, there is paucity of data regarding its usefulness in management of infants with suspected interstitial lung disease. In this paper, we present the contribution of infant pulmonary function testing (iPFT) to the management of two infants with biopsy confirmed chronic pneumonitis of infancy due to surfactant protein C mutation. We have productively and safely used serial iPFT for decision making both during diagnosis and follow‐up of these infants. Pediatr Pulmonol. 2015; 50:E17–E23. © 2015 Wiley Periodicals, Inc.